MENJELAJAHI PENGARUH PENDEKATAN BEHAVIORAL DAN KOGNITIF SOSIAL TERHADAP REGULASI EMOSI DAN KECERDASAN EMOSIONAL - Fauziah Nasution; Natasya Miranda Gihar; Fara Audina Lubis; Juanda Muktar Hasibuan (CV. ADIBA AISHA AMIRA, 2023)
This study aims to explore the influence of social cognitive and behavioral approaches on emotion regulation and emotional intelligence. The behavioral approach focuses on positive reinforcement and punishment techniques that help individuals control emotions and improve social skills. Meanwhile, the social cognitive approach involves understanding and changing mindsets that influence individual emotional responses. This research method uses the literature study method by collecting and analyzing relevant scientific literature. The research findings show that these two approaches have a significant positive impact on improving emotional regulation and individual emotional intelligence. The behavioral approach helps individuals recognize and regulate emotions in challenging situations and improve social skills. The social cognitive approach assists individuals in understanding and evaluating their own emotional responses as well as those of others.